Superalloys 2004 (Tenth International Symposium) 2004
DOI: 10.7449/2004/superalloys_2004_897_906
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Microstructure-Explicit Model of Creep in Nickel-Base Superalloys

Abstract: Past approaches to modelling the creep behaviour of engineering alloys have been either totally empirical or, while having functional forms consistent with current understanding of deformation and fracture mechanisms, have been calibrated by comparison with an available creep database. They have not specifically included quantitative measures of the microstructural features that are thought to impart creep resistance to the alloys. The present paper reviews and extends a microstructure-specific model of creep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Sophisticated experimental work has been performed to characterise and rationalise the creep behaviour in regimes of high temperatures and applied stresses to study the role of diffusion [1], the effect of misorientation [2], the role of rafting [3,4], as well as the origins of primary creep [5]. In parallel, microstructure modelling has been conducted to understand the detailed micro-mechanical behaviour and to predict creep deformation using crystal plasticity based modelling [6,7] or constitutive based modelling [8 -10].…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated experimental work has been performed to characterise and rationalise the creep behaviour in regimes of high temperatures and applied stresses to study the role of diffusion [1], the effect of misorientation [2], the role of rafting [3,4], as well as the origins of primary creep [5]. In parallel, microstructure modelling has been conducted to understand the detailed micro-mechanical behaviour and to predict creep deformation using crystal plasticity based modelling [6,7] or constitutive based modelling [8 -10].…”
Section: Introductionmentioning
confidence: 99%
“…The plasticity model is based on the von Mises effective stress with a nonlinear mixed isotropickinematic hardening rule as described by Dodds [30]. The creep model follows the physics-based modeling of dominant deformation mechanisms similar to the approaches of Ashby, Dyson, McLean and others [13,[21][22][23][24]. Based on the SEM and TEM observations of the shot peened and thermally exposed microstructure, it has been argued that the microstructure remains stable over the range of temperatures and exposure times in this study [38].…”
Section: Coupled Creep-plasticity Modelmentioning
confidence: 99%
“…Initial approaches to represent material degradation under creep loading include the continuum damage mechanics (CDM) approaches of Kachanov [16] and Rabotnov [17] that incorporate a single damage parameter and associated evolution equation. More recently, the simple damage parameters in the CDM approach have been replaced by specific degradation models representing mechanisms such as cavity nucleation and growth, subgrain coarsening, multiplication of mobile dislocations, and thermally and environmentally driven mechanisms [18][19][20][21][22][23][24].…”
Section: Creep Deformation Mechanisms and Modelsmentioning
confidence: 99%
“…The current state-of-the-art in CDM methodology recently has been described [34] and, because it can be shown that other wellknown methods such as the Larson-Miller parameter and the Omega parameter can be derived from a CDM analysis, it is evident that this methodology provides a unifying framework within which apparently unrelated life-prediction methods can be rationalized. The application of the technique in the prediction of the creep behavior of superalloys [35], and of ferritic steels and simple power plant components [36], recently has been described.…”
Section: Prediction Of Materials Properties By Computer Modelingmentioning
confidence: 99%